Трансакційні витрати на макро-, мезо- та мікрорівнях - Грицаєнко, Микола Ігорович; Грицаенко, Николай Игоревич; Hrytsaienko, Mykola (My University, 2018)
UK: На основі опрацювання наукових джерел визначена сутність трансакційних витрат та проведена їх оцінка на макро-, мезо- та мікроекономічному рівнях. Узагальнені різноманітні трактування поняття «трансакційні витрати». Сформульована авторська дефініція трансакційних витрат як таких, що збільшують ціну товару, не змінюючи його споживчої вартості, що виникають внаслідок взаємодії підприємств з іншими суб’єктами інституційного середовища. Запропонована оцінка трансакційних витрат національної економіки (макрорівень) та регіонів (мезорівень) через оцінювання розміру відповідного трансакційного сектору. Проаналізована динаміка розміру трансакційного сектору регіонів, його вплив на валовий регіональний продукт. Зроблений висновок про те, що недостатній розмір частки трансакційного сектору в структурі валового регіонального продукту може свідчити про глибоку економічну кризу та наявність деструктивних зрушень в економіці. Трансакційні витрати галузі (мезорівень) запропоновано визначати через суму трансакційних витрат підприємств відповідної галузі. Зроблений підрахунок трансакційних витрат сільського господарства. Оцінку трансакційних витрат підприємства (мікрорівень) зроблено на прикладі декількох типових сільськогосподарських підприємств різних організаційно-правових форм господарювання Запорізької області. Зроблений загальний висновок про те, що розвиток трансакційного сектору має позитивно впливати на розмір ВРП, стан економіки регіонів і країни в цілому. Збільшення до певних меж трансакційних витрат як окремих підприємств, так і галузей у цілому сприятиме підвищенню ефективності виробництва. RU: На основе изучения научных источников определена сущность трансакционных издержек и проведена их оценка на макро-, мезо- и микроэкономическом уровнях. Обобщены различные трактовки понятия «трансакционные издержки». Сформулирована авторская дефиниция трансакционных издержек как таких, что увеличивают цену товара, не меняя его потребительской стоимости, возникающих в результате взаимодействия предприятий с другими субъектами институциональной среды. Предложена оценка трансакционных издержек национальной экономики (макроуровень) и регионов (мезоуро- вень) на основе оценки размера соответствующего трансакционного сектора. Проанализирована динамика размера трансакционного сектора регионов, его влияние на валовой региональный продукт. Сделан вывод о том, что недостаточный размер доли трансакционного сектора в структуре валового регионального продукта может свидетельствовать о глубоком кризисе и наличии деструктивных сдвигов в экономике. Трансакционные издержки отрасли (ме- зоуровень) предложено определять через сумму трансакционных издержек предприятий соответствующей отрасли. Произведен подсчет трансакционных издержек сельского хозяйства. Оценку трансакционных издержек предприятия (микроуровень) проведено на примере нескольких типичных сельскохозяйственных предприятий различных организационно-правовых форм хозяйствования Запорожской области. Сделан общий вывод о том, что развитие трансакционного сектора должно положительно влиять на размер валового регионального продукта, состояние экономики регионов и страны в целом. Увеличение до определенных пределов трансакционных издержек как отдельных предприятий, так и отраслей в целом будет способствовать повышению эффективности производства. EN: The development of market relations contributes to the inevitable expansion of the scope of the circle. The deepening of the division of labor, which contributes to the increase of production, simultaneously increases the costs associated with the exchange, quality assessment, measurement of parameters of objects of exchange, control over personnel, etc. That is why the expansion of the scale of exchange inevitably leads to an increase in the absolute value of transaction costs, which affects the effectiveness of the relationship between the entities of the economic system (economic agents) in the process of their economic activity. Hence the urgent need to consider the role and significance of transaction costs in the modern economy. The main purpose of the article is to determine the nature and assessment of transaction costs at the macro-, mezo- and microeconomic levels. In the article on the basis of working out of scientific sources generalized various interpretations of the concept of "transaction costs". The author's definition of transaction costs is formulated as increasing the price of a product without changing its consumer value arising from the interaction of enterprises with other subjects of the institutional environment. Transaction cost management requires their assessment at macro-, mezzo- and micro- levels. The proposed transaction costs of the national economy (macro level) are determined by the size of the transactional sector of the economy, which includes the inclusion of wholesale and retail trade; repair of motor vehicles and motorcycles; transport, warehousing, postal and courier activities; temporary placement and organization of food; information and telecommunications; financial and insurance activity; real estate transactions; administrative and auxiliary services activities; public administration and defence; compulsory social insurance. Transaction costs of the region (mezzanine) should be estimated in the same way as the transaction costs of the national economy as a whole. The dynamics of the size of the transactional sector of the regions, its influence on the gross regional product is analysed. The size and structure of the transactional sector of the Zaporizhzhya region is analysed in more detail. It is concluded that the insufficient size of the share of the transactional sector in the structure of the gross regional product may indicate a profound economic crisis and the existence of destructive changes in the economy. Transaction costs of the industry (mezzanine) are proposed to be determined through the transaction costs of the enterprises concerned. Calculated transactional costs of agriculture in Ukraine. The impact of transaction costs on the value of gross value added of agriculture, forestry and fisheries is determined. An estimation of transaction costs of the enterprise (micro level) is made on the example of several typical agricultural enterprises of various organizational and legal forms of management of the Zaporizhzhya region. The analysis revealed a direct proportional relationship between the size of the net income from the sale of agricultural products and services and transaction costs. To calculate the difference between the full and the production cost of products, the following elements of costs included in the production cost are added: deductions for social measures; payment for services and works performed by outside organizations, and other material expenses; other expenses, including rent. As a result, the article concludes that the development of the transactional sector should positively influence the size of the gross regional product, the state of the economy of regions and the country as a whole through stimulating the intensive growth of the number of ties, relations, interactions and transactions, accompanied by an increase in the overall transaction costs At the same time, the increase to certain limits of transaction costs of both individual enterprises and industries in general stimulates their development, contributes to increasing the efficiency of production. Prospects for further research are the search for factors that influence the efficiency of functioning of the transactional sector of the economy and accordingly reduce transaction costs.
Трансакционные издержки на макро-, мезо- и микроуровне
Transaction costs on macro-, mezo- and microrives
Keywords: трансакційний сектор економіки; трансакційні витрати країни; валовий внутрішній продукт; трансакційні витрати регіону; валовий регіональний продукт; трансакційні витрати галузі; трансакційні витрати сільського господарства; трансакційні витрати сільськогосподарського підприємства; трансакционный сектор экономики; трансакционные издержки страны; валовой внутренний продукт; трансакционные издержки региона; валовой региональный продукт; трансакционные издержки отрасли; трансакционные издержки сельского хозяйства; трансакционные издержки сельскохозяйственного предприятия; transactional sector of economy; transaction costs of the country; gross domestic product; transaction costs of the region; gross regional product; transaction costs of the industry; transaction costs of agriculture; transaction costs of the agricultural enterprise